2013
DOI: 10.4168/aair.2013.5.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Diseases Concomitant With Asthma in Middle-Aged and Elderly Subjects in Korea: A Population-Based Study

Abstract: PurposeAsthma is prevalent in many countries. Few studies have investigated the association between asthma and concomitant diseases. We retrospectively analyzed the fourth Korean National Health and Nutrition Survey database, performed in 2008 using nationwide stratified random sampling to obtain a representative cohort of the Korean population.MethodsWe evaluated the association between both self-reported ever-asthmatics and wheezers and concomitant diseases such as arthritis, hypertension, gastrointestinal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…Such a relationship is also seen between asthma and other markers of the metabolic syndrome such as insulin resistance and hypertension that cannot be accounted for by increased body mass alone [47]. While both obesity and asthma are individually associated with an increased state of inflammation [8], interestingly, in obese asthmatics, there is a dissociation between cellular inflammation and severity of symptoms, especially in women [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Such a relationship is also seen between asthma and other markers of the metabolic syndrome such as insulin resistance and hypertension that cannot be accounted for by increased body mass alone [47]. While both obesity and asthma are individually associated with an increased state of inflammation [8], interestingly, in obese asthmatics, there is a dissociation between cellular inflammation and severity of symptoms, especially in women [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is associated with DT2 and obesity [37,38], both of which are metabolic disorders with an underlying systemic inflammatory profile. Together with our data, this suggests that systemic inflammation associated with allergy may modify insulin signaling in the brain, which could have consequences for brain function and the pathophysiology of some neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The article in the issue evaluated comorbid diseases in asthma and demonstrated that arthritis, rhinitis, depression and obesity were independently associated with both self-reported asthma and wheezing in adults older than 40 years of age 4. These results were statistically supported because the authors adjusted for confounding factors and other chronic diseases compared to previous studies.…”
mentioning
confidence: 85%
“…At least five phenotypes of asthma have been proposed 7. In the article in the issue,4 asthma was described as a disease characterized by eosinophilic and Th2 type inflammation. However, it is now known that inflammation in asthma is actually more complex.…”
mentioning
confidence: 99%